Early Initiation and Prevalence of Exclusive Breastfeeding: A Cross-sectional Study among Employed Mothers in Bantul District, Indonesia - Ervina, Mia; Paramashanti, Bunga Astria; Hadi, Hamam; Rahmawati, Nur Indah (Journal of Nepal Paediatric Society, 2020)
Introduction: Exclusive breastfeeding plays an important role in preventing morbidity and mortality in infants and young children. However, exclusive breastfeeding coverage remains low, especially among working mothers. This study aimed to examine the relationship between early initiation of breastfeeding and prevalence of exclusive breastfeeding among working mothers in Bantul District, Yogyakarta Special Region, Indonesia. Methods: This study used a cross-sectional design. The population were all women in reproductive age who worked in middle and large companies. Samples included mothers whose infants were aged six to 12 months and were selected by probability proportional to size sampling technique. Main outcome was exclusive breastfeeding, while the independent variable was the early initiation of breastfeeding. Statistical analysis were descriptive statistics test, chi-square test, and multiple logistic regression at the level of significance of 0.05. Results: Exclusive breastfeeding coverage was around 22%, whilst the early initiation of breastfeeding coverage was 10%. Early initiation of breastfeeding was associated with exclusive breastfeeding practice (adjusted OR = 2.93; 95% CI: 1.04 - 8.28). Variables that were not significantly related to exclusive breastfeeding included being a first-time mother, maternal age, maternal educational level, breastfeeding counselling during antenatal visits, and delivery methods. Conclusions: Early initiation of breastfeeding is associated with higher prevalence of exclusive breastfeeding among working mothers. To increase exclusive breastfeeding coverage, particularly among employed women, it is highly recommended to enhance early initiation of breastfeeding program.